Analisis Kurikulum Merdeka: Mampukah Merevitalisasi Bahasa Daerah? - Zaki Chandra (Journal of Information Systems and Management (JISMA), 2023)
This scholarly work discusses the importance of revitalizing regional languages as an effort to protect and preserve Indonesia's cultural heritage. The discussion of regional language revitalization is crucial because it is suspected that regional languages are at risk of extinction. The extinction of regional languages has implications for Indonesia's diversity, identity, and history. In this research report, a qualitative descriptive method was employed, involving data collection through audio transcripts of oral narratives from the YouTube video "Merdeka Belajar Episode 17: Revitalisasi Bahasa Daerah," provided by the Ministry of Education and Culture of the Republic of Indonesia channel. The results of this study outline five strategic steps for the protection of regional languages, which can be adapted to the unique conditions of each language: mapping, vitality assessment, conservation, revitalization, and registration. The revitalization program targets language communities, teachers, school principals, supervisors, and students. Various flexible teaching methods and approaches are utilized to ensure the success of this program. In 2022, 38 regional languages in 12 provinces became the focus of revitalization efforts, with approaches tailored to the sustainability of each language. Regional language revitalization is one of the essential programs in preserving Indonesia's cultural diversity.